Crashing Analysis on the Construction of The First Its Tower Building Using Time Cost Trade Off Method - Lindah Sri Aminingtiyas; Koespiadi; F Rooslan Edy Santosa (Journal of World Conference (JWC), 2021)
A construction project is a series of activities carried out with a specific scope of work, time and expense according to the agreement between the project owners and the contractors. In the case of a project, it is necessary to file a task so that it can run smoothly and carry out according to plan times. An optimum time and expense analysis of the job involved time cost trade off for case studies of the advanced construction of the tower's 1 (one) located on the campus of ITS Sukolilo - Surabaya. Analysis runs to speed up project time that is tardiness with minimal costs added and should be noted on the other hand that the emphasis on activities that are on critical trajectories and have the lowest cost slope on those tracks. Steps made in this acceleration are identifications of job activity, arranging network diagrams, specifying acceleration scenarios, crashing duration and crashing cost, calculating cost slope, and do the iteration phase. After a time cost trade off analysis, it would provide output with multiple time and cost alternatives to the new project. Of the many alternatives, selected the time and expense of the completion of the project optimum. From the analysis, to complete the work at completion time according to plan, the cost increased by IDR 474.268.897,00 from IDR 9.919.982.348,00 to IDR 10.394.251.245,00 with a 32 day reduction from 180 days to 148 days so that the project could be completed as expected on March 2, 2021.